(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
about the life and work of Maqsud Shaykhzoda, about his entry into Uzbekistan and acquaintance with the famous writers here, about his creations during the war years. His works embody the floral echo of a burning soul, which lived with great revolutionary ideals, vivid patriotic feelings, truly creative emotions